Rethinking transdermal drug delivery using PVA-NLC based films. (16th September 2021) - Solís, Airam Cobo; Bento, Daniel; Nunes, Sandra; Valente, Artur; Pais, Alberto; Vitorino, Carla
Abstract: This work aims at designing an innovative poly(vinyl alcohol) (PVA) adhesive film containing nanostructured lipid carriers (NLC) loaded with olanzapine (OL) and simvastatin (SV), for the treatment of psychiatric disorders. Drug-in-NLC-in-PVA transdermal films were developed following a 3 2 full factorial planning. PVA concentration and lipid content were considered as key formulation variables. NLC formulations exhibited an average size of 177 ± 2 nm with a polydispersity index of 0.3 and a zeta potential of −20.8 ± 0.6 mV. The performance of PVA-NLC films was assessed in terms of adhesion, mechanical and transport (release and permeation) properties to obtain the best product conditions and providing a sustainable development process. Release kinetic studies showed that the PVA-NLC films enable a controlled drug release and that it depends on the concentration of PVA used. The formulation containing 12% (w/w) of PVA and 15% (w/w) of NLC provided the best permeation rate, along with adequate adhesiveness and cohesiveness, which is considered a promising therapeutic approach for further pre-clinical studies. An insight on the molecular details that govern the film construction and respective performance was provided by molecular dynamics simulations. Graphical abstract: Image 1 Highlights: A differentiated drug-in-NLC-in-PVA film design for transdermal delivery was developed. PVA-NLC films exhibited mechanical and adhesive properties suitable for skin application. The NLC prompted prolonged drug release, being influenced by the PVA concentration. The formulation containing 12% PVA-15% NLC provided the best permeation rate. MD simulations supported the compatibility among film components.